Environmental Impact Analysis Using Life Cycle Assessment (LCA) on Plastic Waste Processing at Antang Makassar Landfill - Amrul, Amrul; Chairany, Nurul; Pawennari, Andi; Nur, Taufik (PT. SAFARI AMALIA, 2025)
This study analyzes emission loads generated from plastic waste shredding activities around the Antang Landfill. The process involves the use of transportation vehicles, diesel engines, polypropylene sacks, and polyethylene terephthalate (PET) packaging from used cooking oil containers. Diesel combustion and transportation activities contribute to air pollution, while shredded plastic waste may release additional emissions into the environment. The research aims to evaluate the environmental impacts of plastic waste shredding and propose strategies for sustainable waste management. The Life Cycle Assessment (LCA) method was applied to assess environmental aspects and potential impacts through input–output inventory analysis. Data were processed using SimaPro software, with impact assessment conducted through categorization and normalization stages. The findings reveal three main impact categories: global warming, ozone layer depletion, and human toxicity. The collection stage contributes most to human toxicity (4.66E-5 and 2.48E-16), while the transportation stage produces the highest emissions from operational vehicles (8.12E-5 and 4.32E-16). During the shredding stage, diesel combustion contributes most to ozone layer depletion (1.02E-8) and human toxicity (2.52E-13). The plastic fragment handling stage shows significant impacts on ozone layer depletion (7.9E-9) and global warming (8.69E-13). Further research is recommended to develop emission reduction strategies that integrate cost efficiency and stakeholder participation.